Poverty Alleviation in the Quran: A Study of Al Adaby Al Ijtima'i - Muttakhida, Istna Aliya; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
Poverty that has existed since man was created is one of the major problems for humans, not only has an impact on social and economic problems but more especially can have an impact on religious beliefs, even to the point of mortgaging faith with a world treasure. Although poverty can be said to be the destiny of the creator, but as an intelligent creature, especially as a Muslim, of course, in addition to having to be able to accept that fate, it must also be accompanied by maximum efforts to get out of the poverty zone. The topic of poverty here is poor in property and of course this problem has a solution. This research is described in the style of adaby ijtima'i, which is to elaborate the verses of the Quran in accordance with the problem that is currently plaguing society, namely poverty . This study will explain ways of poverty alleviation based on factors and in accordance with the content of the holy verses of the Quran which are expected to be a foothold out of the poverty zone.